2010
DOI: 10.1097/ico.0b013e3181d0092c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anterior and Posterior Corneal Surface Irregularity in Descemet Stripping Automated Endothelial Keratoplasty and Penetrating Keratoplasty

Abstract: Postoperative corneal irregularity of the anterior surface was greater after PK than after DSAEK, whereas there was no significant difference in posterior surface irregularity. DSAEK is superior to PK in terms of the higher-order irregularity of the anterior surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 31 publications
(30 reference statements)
2
30
2
Order By: Relevance
“…138 Posterior corneal HOAs were found to be significantly greater post-DSAEK than in normal eyes. 138 This study also demonstrated no significant difference in anterior HOAs between normal and post-DSAEK corneas, although there was a trend for greater anterior HOAs in the DSAEK group, 138 possibly representing a type 2 error.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
See 3 more Smart Citations
“…138 Posterior corneal HOAs were found to be significantly greater post-DSAEK than in normal eyes. 138 This study also demonstrated no significant difference in anterior HOAs between normal and post-DSAEK corneas, although there was a trend for greater anterior HOAs in the DSAEK group, 138 possibly representing a type 2 error.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
“…5 Guerra et al reported that only 23% of DSAEK patients achieved VA >20/25 at 12 months follow-up, despite having otherwise healthy eyes and clear corneas with no evidence of graft failure, 44 and similar results with EK have been found by several others. 72,77,108,138 . Possible explanations for this include optical degradation at the graftrecipient interface, 64 increased corneal thickness, increased high order aberrations, stromal scarring and fibrosis secondary to the underlying pathology, and increased light scatter.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DSAEK has several advantages over penetrating keratoplasty (PK), such as rapid visual recovery, less postoperative astigmatism, fewer higher-order aberrations (HOAs) and a decreased rejection rate [3][4][5][6], not all patients achieve greater visual acuity, despite the improved corneal clarity DSAEK provides. The reasons for poor visual acuity after DSAEK include HOAs and interface or subepithelial opacities [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%